Experimental study on mechanical drilling of carbon/epoxy composite-Ti6Al4V stacks. Issue 7 (19th May 2019) - Xu, Jinyang; Zhou, Lei; Chen, Ming; Ren, Fei
ABSTRACT: This paper concerns the experimental studies on the drilling process of multilayer carbon/epoxy composite-Ti6Al4V stacks and their individual material layers using tungsten carbide drills. The significance of the current work aims to reveal the impact of tool wear on the drilling process for CFRP/Ti6Al4V, CFRP and Ti6Al4V. Four groups of machining tests including drilling individual CFRP, individual Ti6Al4V, multilayer CFRP/Ti6Al4V stacks with and without a cooling treatment were conducted. Drilling forces, cutting temperatures and hole quality attributes were experimentally investigated in terms of the drill wear extents. The mechanism controlling the tool wear effect on the drilling machinability of CFRP/Ti6Al4V was revealed, providing several implications for the industrial manufacturers. The results highlight the significant impact of the titanium chip ejection on the composite surface quality and the necessity of a rigorous tool wear control to guarantee the damage-free drilling of CFRP/Ti6Al4V stacks.